“Due regard” obligations toward nuclear wastewater discharge from the perspective of sustainable development of the marine environment - Xiao, Wan (Frontiers in Marine Science, 2024)
The events of the 2011 Fukushima nuclear accident in Japan have garnered global concern. Despite nuclear power plants addressing numerous energy challenges, they poses substantial risks to environmental safety. The global legal basis to fulfill due regard obligations toward nuclear wastewater discharge involves international nuclear energy and marine environmental protection laws. There is substantive scope of due regard obligations toward nuclear wastewater discharge, including fulfilling international duties, prohibiting marine environmental pollution, preventing transboundary harm, and ensuring procedural obligations. The procedural obligations encompass timely notification of nuclear pollution, scientific assessment, and active consultation and cooperation with the international community. As there are still numerous obstacles to the application of due regard in the discharge of nuclear wastewater, the international marine environment frequently suffers from nuclear pollution. Considering the potential for transboundary environmental harm owing to the discharge of nuclear wastewater, this paper proposes effective solutions to this issue from the perspective of sustainable development of the marine environment. These solutions include formulating specific normative guidelines, clarifying liability for paying transboundary harm compensation, developing unified international assessment standards, and establishing an international platform for mandatory cooperation. Such solutions reinforce the national responsibility of all countries to actively fulfill their due regard obligations and effectively resolve the issue of potential irreversible damage to the marine environment. Additionally, the paper provides suggestions regarding how the international community can address the issue of Japan's nuclear wastewater discharge and other similar issues that may arise.